2021
DOI: 10.3332/ecancer.2021.1180
|View full text |Cite
|
Sign up to set email alerts
|

The impact of national non-pharmaceutical interventions (‘lockdowns’) on the presentation of cancer patients

Abstract: One of the most ignored aspects of the COVID-19 pandemic has been the impact of public health measures by governments on wider health and welfare. From March 2020, hospitals in the UK saw a dramatic reduction in patients with cancer presenting due to multifactorial reasons. The impact of the pandemic on patients with cancer in the South East London Cancer Alliance was studied. The specific aims were (1) to examine the reduction in cancer diagnoses during the first wave of the pandemic and (2) to examine the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…It should be noted that our estimates are very conservative with regards to the health and economic impact. Recent data [5] suggest that the drop in expected cancer diagnoses based on yearly estimates is far greater than the estimates we have made in this paper [14]. For example, for bowel cancer between April to October 2020, over 3500 fewer people had been diagnosed and treated for colorectal cancer in England than would have been expected [7].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It should be noted that our estimates are very conservative with regards to the health and economic impact. Recent data [5] suggest that the drop in expected cancer diagnoses based on yearly estimates is far greater than the estimates we have made in this paper [14]. For example, for bowel cancer between April to October 2020, over 3500 fewer people had been diagnosed and treated for colorectal cancer in England than would have been expected [7].…”
Section: Discussionmentioning
confidence: 51%
“…In the UK, following the first wave of the pandemic, up to 3 million men and women did not receive screening investigations due to suspension of these services, fewer patients were referred with suspected cancers [1], and 3.2 million fewer investigations (e.g., colonoscopy, cystoscopy, gastroscopy, CT scans, MRI between March and July 2020) were performed due to cancellation or deferral [2,3]. This decrease in referrals and diagnostic investigation implies an eventual later diagnosis with more advanced-stage cancer, which will have a direct impact on long term prognosis [4,5]. As well as diagnostic pathways, it has also become rapidly apparent that treatment delays [6], especially for cancer surgery, were also occurring [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it was noted that there was an increase in the proportion of patients with stage IV disease being treated in 2020 when compared to 2019. We postulate that these numbers reflect the backlog of undiagnosed cancer cases early on in the pandemic in 2020 [ 7 ]. Furthermore, there was a lower proportion of patients receiving chemotherapy in 2020 when compared to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only study to have analyzed cancer data based on pathology results in Spain observed a 17% reduction in diagnoses, this finding being similar to those of other studies [ 15 , 16 ]. These figures reflect the effort to recover care services, especially oncology referrals, despite their saturation after reaching a 70% reduction in activity during the first wave, as other studies have shown [ 17 , 18 , 19 ]. In addition, despite there being less activity in the pathology departments during COVID-19 than during 2019, the probability of neoplasia diagnosis during the pandemic has been statistically significantly higher.…”
Section: Discussionmentioning
confidence: 76%